ChemInform Abstract: Photocatalysts in Polymerization Reactions. Issue 27 (16th June 2016) - Zivic, Nicolas; Bouzrati‐Zerelli, Mariem; Kermagoret, Anthony; Dumur, Frederic; Fouassier, Jean‐Pierre; Gigmes, Didier; Lalevee, Jacques
Abstract: Review: [136 refs.